Metabolic profile and post-operative outcomes in contemporary patients with peripheral arterial disease and critical limb ischaemia - Wu, Lily (Department of Surgery, 2018)
Background: Peripheral arterial disease (PAD) is an established occlusive disease of the peripheral arteries and is not uncommon in the elderly. Atherosclerosis accounts for 90% of the pathology. Only 15% of affected individuals become symptomatic. Most symptomatic individuals present with intermittent claudication (IC). Only a small proportion (1%) of affected individuals present with critical limb ischaemia (CLI). Revascularization aimed at limb salvage, and recovery of ambulation and independent living is the ultimate therapeutic option for the advanced form of PAD (CLI). Traditionally, the success of revascularization for CLI has been defined by graft patency rates and limb salvage rates. Functional outcomes such as ischaemic wound healing and recovery of ambulatory function for independent living have been the focus in more recent publications. However, these assessments do not consider the patients' pre-operative metabolic profile as a predictor of postoperative outcomes. Purpose: The purpose of this study was to determine, in a prospective manner, the influence of preoperative metabolic profile on post-operative outcomes in contemporary patients with peripheral arterial disease presenting with critical limb ischaemia at a tertiary hospital in South Africa. Methods: All consecutive patients, ≥ 18 years, with CLI admitted to the vascular unit at Groote Schuur Hospital over a two-year period (1st January, 2015 to 31st December, 2016) with reconstructable disease were recruited for the study. Written informed consent was obtained from all participants. Revascularization entailed either open surgical revascularization, endovascular interventions or both (hybrid procedures). Data was analyzed according to the clinical level of disease and the type of surgical intervention. Post-operative outcome measures were determined. Primary endpoints (functional and technical outcomes) • Ambulatory recovery at six months and one year • Complete ischaemic wound healing at six months and one year • Limb salvage rate at six months and one year • Primary graft patency rate at six months and one year Secondary endpoint • The influence of pre-operative metabolic profile on the post-operative outcomes The association between pre-operative metabolic profile and post-operative outcomes was determined by Pearson Chi-square statistical test and logistic regression model. Results: A total of 73 consecutive patients were recruited for this study with a mean age of 58 ± 9 years (Range: 30 - 75 years). Seventeen patients (23.3%) had rest pain and 56 (76.7%) had tissue loss [Minor tissue loss was 47 (64.4%) and major tissue loss was 9 (12.3%)]. Current smokers and previous smokers constituted 86% of the sample population with a male to female ratio of approximately 1:1. Our study population was generally overweight based on the BMI. There was high prevalence of abdominal obesity and high body fat for both males and females. Recovery of ambulatory status was 69% and 67% at six months and one year follow-up respectively. The rate of ischaemic wound healing at six months and one year was 48.2% and 75.0% respectively. Surgical site sepsis was the most common local wound complication. Limb salvage rate was 78% and 79% at six months and one year respectively. Overall primary graft patency at six months was 69.0% but reduced to 60.0% at one year. Major amputation rate at one year was 21%. Most of the postoperative wound-related complications occurred among patients with diabetes. More diabetic patients had major amputations compared to non-diabetic patients (57.9% vs 42.1%). One year amputation-free survival (AFS) was 69.9%. There were no statistically significant associations between metabolic profile of patients and post-operative clinical outcomes. Conclusion: Demographics, co-morbidities, and procedural details of our study population, reflected a relatively younger population with CLI. The profile of this contemporary vascular surgery patients is that of overweight, high abdominal obesity, and high prevalence of smoking among both gender. The technical and functional outcomes observed in this study are consistent with available western literature. Diabetes was associated with prolonged ischaemic wound healing, higher risk of major amputation and local wound complications. A statistically significant association was not found between patients' metabolic profile and post-operative outcome but this could be due to the small sample size and short follow up period.